"Kids save lives" – School resuscitation programs worldwide and WHO initiative for this. Issue 6 (December 2015) - Ecker, H.; Schroeder, D.C.; Böttiger, B.W.
Abstract: Survival-rates and neurological outcome after out-of-hospital cardiac arrest significantly depends on the period of time until initiation of cardiopulmonary resuscitation (CPR). Considering that the emergency medical arrives 8–12 min after collapse, a desperate need of lay-persons able to perform CPR exists. However, bystander CPR-rates in Europe are alarmingly low. The "Kid-save-lives" initiative is a global call to train youngsters CPR in school to sustainably improve bystander CPR-rates. Thus, a large part of the lay population could be trained in CPR over time, which could save thousands of lives every year. This article provides a brief overview of the scientific knowledge in school resuscitation programs and outlines educational and pedagogical aspects in training of schoolchildren in CPR. Graphical abstract: Highlights: Early CPR improves chances of survival by a factor of 2–4 and can safe nearly 200, 000 lives every year in Europe. Out-of-hospital cardiac arrest survival increased threefold with mandatory BLS-training in Schools in Denmark. WHO endorse "Kids save lives" and advises that schoolchildren from the age of 12 should be trained in CPR for 2 h per year. Health care providers and teachers can instruct BLS for schoolchildren easy and inexpensive. Over time all citizens will act as competent first responders saving lives in cardiac arrest situations.